Linear‐Dendritic Alternating Copolymers. Issue 31 (27th June 2019) - Sun, Haotian; Haque, Farihah M.; Zhang, Yi; Commisso, Alex; Mohamed, Mohamed Alaa; Tsianou, Marina; Cui, Honggang; Grayson, Scott M.; Cheng, Chong
Abstract: Herein, the design, synthesis, and characterization of an unprecedented copolymer consisting of alternating linear and dendritic segments is described. First, a 4th‐generation Hawker‐type dendron with two azide groups was synthesized, followed by a step‐growth azide‐alkyne "click" reaction between the 4th‐generation diazido dendron and poly(ethylene glycol) diacetylene to create the target polymers. Unequal reactivity of the functional groups was observed in the step‐growth polymerization. The resulting copolymers, with alternating hydrophilic linear and hydrophobic dendritic segments, can spontaneously associate into a unique type of microphase‐segregated nanorods in water. Abstract : Spaced‐out dendrons : Step‐growth "click" polymerization using well‐defined linear polymeric and dendritic reactants has led to linear‐dendritic copolymers in which the linear segments serve as uniform spacers between the dendrons. With alternating hydrophilic linear blocks and hydrophobic dendrons, the copolymers can spontaneously self‐assemble into a unique type of microphase‐segregated nanorod in water.